PENDIDIKAN DASAR UNTUK ANAK PENGUNGSI DI INDONESIA: ANTARA REGULASI DAN REALITA - Marjianto, Khoirul Annafi; Alrin Tambunan; Maidah Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a fundamental right guaranteed to every child, including refugee children in Indonesia. Although Indonesia has ratified the Convention on the Rights of the Child (UNCRC) and issued national policies supporting access to education for refugees, implementation still faces various challenges. According to UNHCR data at the end of 2023, there were 12,295 registered refugees in Indonesia, including 3,555 children, of whom 227 were unaccompanied by parents or relatives and 106 were separated from their families, making them the most vulnerable group in terms of fulfilling their right to education. This study aims to analyse the gap between government regulations and the reality of implementing basic education for refugee children in Indonesia. The method used is a qualitative descriptive approach with a documentary study technique on circular letters from the Ministry of Education, Culture, Research, and Technology, UNHCR reports, KPAI data, and other relevant publications. The results of the study show that although regulations such as the Secretary General of Kemendikbudristek Circular Letter No. 75253/A.A.4/HK/2019 have established mechanisms for providing education for refugee children, in reality only a small proportion of children have access to formal education. Out of 1,595 school-age children registered as of 2022, only 646 have accessed formal education, either in public or private schools. The main obstacles include administrative challenges, limited school capacity, lack of budgetary support from the state or local budgets, and insufficient readiness of communities and educational institutions to accept refugee children. Therefore, more technical operational policies, enhanced capacity of educational institutions, and inter-institutional coordination are needed to truly realise inclusive and equitable basic education.